The Modern Bulgarian Woman and the „Family-Work” Collision - Kineva, Todorka (Research Papers, 2016)
The following study presents the “family-work” collision and in particular the role conflicts of the modern Bulgarian woman arising between family and work and how they affect her personal and professional development, social roles, choice of model of female personal realization.The analysis is based on data from an author's empirical research, conducted within the “Role conflicts of the modern Bulgarian woman: between family and career” thesis. The survey was conducted in July-August 2013. The analysis focuses on the following problem-thematic fields:The modern woman between family and work and the influences between the two areas;The model of a modern female personal and professional development, represented by value orientation, beliefs and attitudes of women regarding family and work;The balance between family and professional life, or to what extent modern Bulgarian women manage to achieve a balance between their roles in both areas. The main reasons (not) to achieve a harmonious reconciliation of family and professional roles; The generational affiliation as a factor for family and career realization – specificity for the young and mature generations of women. Positioning of family and work in the course of women’s life.
Keywords: Modern bulgarian woman; Work; Social roles; Balance; Role conflicts; Female personal and professional development; Career; Family